The impact of library automation to organization and personnel as perceived by the library staff in selected academic libraries in Metro Manila a cross-cultural study - San Andres, Willian A. (Institute of Library and Information Science, University of the Philippines Diliman, 2002)
This study aimed to provide information on the impact of information to organization and personnel as perceived by the library staff in selected academic libraries in Metro Manila and how their perceptions differ from the perceptions of other library staff in the United States and Canada.